Airway remodeling and serum total immunoglobulin E (IgE) levels in a murine model of asthma - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2001)
A murine model of allergen-induced airway inflammation, epithelial phenotypic changes, and total immunoglobulin E (IgE) levels is described. Mice were sensitized to ovalbumin without adjuvant and challenged by multiple intratracheal instillations of ovalbumin by a nonsurgical technique. After repeated challenges, the basement membrane of the airway epithelium showed fibrosis, inflammatory cell infiltration at peribronchial and perivascular sites, and goblet cell hyperplasia. In addition, total IgE levels were found to be increased significantly. Further studies which will evaluate the contribution of each feature of remodeled airway to the natural history of asthma are definitely needed.
Keywords: airway remodeling; BALB/c mice; OVA; BRONCHIAL-ASTHMA; WALL; OBSTRUCTION; EOSINOPHIL; EXPRESSION; FIBROSIS